ChemInform Abstract: Diversity Oriented Synthesis of Indoloazepinobenzimidazole and Benzimidazotriazolobenzodiazepine from N1‐Alkyne‐1, 2‐diamines. Issue 18 (April 2016) - Kumar, Ravi; Arigela, Rajesh K.; Samala, Srinivas; Kundu, Bijoy
Abstract: A one‐pot protocol for the synthesis of two types of N‐polyheterocycles is developed.